Effect of Feeding Feed Blocks Enriched with Different Sources of Protein on the Performance of Awassi Ewes during Late Pregnancy, Suckling and Milking Stages - Ibrahim, Hadeel K. (The Iraqi Journal of Veterinary Medicine, 2008)
Two experiments were conducted to investigate the effect of feeding feedblocks (FB) enriched with different sources of protein on the performance ofAwassi ewes during late pregnancy, suckling and milking stages. Experiment(1) was conducted to investigate the effect of feeding feed blocks enriched withdifferent sources of protein on the performance of Awassi ewes during latepregnancy. Eighty pregnant Awassi ewes (mean live weight 09.91±0.31 Kg),aged 3-5 years were allocated into four groups according to ewes’ live weight.First group (T1) fed ordinary high energy FB (OFB) + straw (ad-libitum). Thesecond group (T2) fed FB enriched with cottonseed meal (FBCSM) + straw (adlibitum).The third group (T3) fed FB enriched with sunflower seed meal(FBSSM) + straw (ad-libitum). The fourth group (T4) fed barley grains + straw(ad-libitum) (Farmer practice). Experiment (2) was conducted to investigate theeffect of feeding high energy feed blocks enriched with different sources ofprotein on the performance of Awassi ewes during suckling and milking stages.Sixty-four Awassi ewes (mean live weight 03.62 ±1.13 kg), aged 3-5 years wereallocated into four groups according to ewes’ live weight and milk yield. Firstgroup (T1) fed OFB + barley grains + straw (ad-libitum). The second group(T2) fed FBCSM + barley grains + straw (ad-libitum). The third group (T3)FBSSM + barley grains + straw (ad-libitum). The fourth group (T4) fed barleygrains + straw (ad-libitum) (Farmer practice). The experimental diets were fedduring the last six weeks of pregnancy, 90 days during suckling stage and 45days during milking stage. The results of Experiment 1 indicated that despite nosignificant differences between the four groups on studied traits (ewes weightchanges and lambs birth weight), but there was a trend the groups (T1, T2 andT3) fed FB performed better than group T4 fed according to the farmer’spractice. Group T2 that was fed FBCSM had slightly better performance thangroups T1, T3 and T4, which were fed OFB, FBSSM and farmer, practice dietsrespectively.